LOCAL WISDOM-BASED TOURIST VILLAGE ORGANIZATION IN LOMBOK TOURIST AREA - Suryani, Any; Irfan, Mohammad (E-Journal of Cultural Studies, 2016)
The development of tourist villages has created tourism-based economic activities, reducing the number of people who intend to move from the rural area to the urban area ‘urbanization’. The local potentials which a village has can grow and develop if the sources it has are effectively used to support the economic and socio-cultural growth and development. If the villagers feel that the tourist attractions they have in their village can improve their prosperity, they will be indirectly made to love their culture; as a result, attempts will be made to conserve and empower the uniqueness and local values they have. Therefore, they should be involved. In this present study, the Tourist Villages used as the object of the study is Sade Traditional Village, Pujut District, and Segenter Traditional Village, Bayan District, North Lombok Regency. Based on the empirical methodology and the qualitative approach used, several conclusions could be drawn. They are the traditional village should be involved in the management of the tourist assets, meaning that the local villagers, for example, should be actively involved in the parking management; the tourists’ interests should be synergized with the local people’s; proactive actions should be taken by all the stakeholders. The traditional law ‘awig-awigadat’ should be improved to support tourism; a good atmosphere of traditional tourism should be created; accesses should be made for the local entrepreneurs to developing whatever is needed by the traditional tourism.
Keywords: organization, village tourism, local wisdom, culture, tradition